THE ROLE OF ENTREPRENEURSHIP IN THE ECONOMIC AND SOCIAL DEVELOPMENT OF UZBEKISTAN - Toshaliyeva, Saodat Tokhirovna (PhD); Avazov, Abdulla Turgunovich (Educational Research in Universal Sciences, 2023)
In this article, in the field of protection of the rights of entrepreneurs - the creation of an effective system of support for business entities, especially during the period of establishing their activities, private entrepreneurship in many ways affects the rate of economic growth, it is said that it is one of the leading sectors that determine the state of population employment, the structure and quality of the gross domestic product.